A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Evaluation and characterization of aphid (Aphis craccivora) resistance in selected alfalfa genotypes - Xin Jiang; Jing Tian; Gang Li; Guy Smagghe; Zhong-Yi Li; Dao-Chao Jin; Zhou Li; Rui Dong; Xin-Yao Gu (Crop Protection, 2026)

Energy input rate as a key switch: tuning product distribution and carbon structure in waste tire pyrolysis via conventional and microwave heating - Peng Liu; Shuxiao Wang; Jing Gu; Rui Shan; Yanzhi Sun; Junqing Pan; Haoran Yuan; Yong Chen (Fuel, 2026)

Grain-size controls on quartz OSL sensitivity in fluvial systems: insights from transport mechanisms in the upper Yellow River - Ya Liu; Song-Xi Du; Jia-Fu Zhang; Xue Rui; Yu-He Shen; Jia-Jing Wang; Qing-Hao Ma; Zheng-Hao Gu (Geomorphology, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Soluble TREM1 Contributes to Aging-Related Neurodegeneration via ROBO2/ERK Pathway - Jing-Wen Qi; Xin-Yu He; Yu-Cheng Gu; Zi-Jian Luo; Rui Duan; Ying-Dong Zhang; Yi Xie; Teng Jiang (Molecular Neurobiology, 2026)

DoLPHiN: a proposed architecture and technical implementation of a database of structural and functional properties of natural polysaccharides with health benefits - Yefu Xin; Yongling Cao; Shuheng Yang; Junhao Hu; Miao Tian; Jian Dai; Jing Shi; Bingcong Yu; Nike Gu; Xiangxu Hu; Rui Zhu; Qianni Duan; et al. (Food Chemistry, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Pig bedding biochar enhances the Cd extraction capacity of Perilla frutescens by mitigating the toxicity of Cd-contaminated soil - Tianlian He; Xingyu Hao; Rui Jing; Zhenguo Li; Ying Chen; Mingwei Yang; Chengzhen Gu; Yulin Wang; Ruiyu Lin; Xinyu Zheng (Journal of Environmental Sciences, 2025)

Comparative study on the effect of H2O/air/CO2 on the gasification results of wheat straw - Shuxiao Wang; Dexin Kong; Rui Shan; Jing Gu; Haoran Yuan; Yong Chen (Biomass and Bioenergy, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Advances in thermochemical valorization of biomass towards carbon neutrality - Jun Zhang; Jing Gu; Rui Shan; Haoran Yuan; Yong Chen (Resources, Conservation and Recycling, 2025)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Fe-Zn bimetallic oxide functionalized biochar for enhanced adsorption of enrofloxacin in water - Guodong Hong; Rui Shan; Jing Gu; Taoli Huhe; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2024)

Catalytic reforming of polypropylene to produce hydrogen: Influence of support characteristics and active metal type in catalyst - Shuxiao Wang; Yibo Sun; Rui Shan; Jing Gu; Haoran Yuan; Yong Chen (Fuel, 2024)

Co-pyrolysis of textile dyeing sludge/litchi shell and CaO: Immobilization of heavy metals and the analysis of the mechanism - Danni Li; Rui Shan; Jing Gu; Yuyuan Zhang; Xianhai Zeng; Lu Lin; Haoran Yuan; Yong Chen (Waste Management, 2023)

Mechanistic insight into the hydrogen transfer pathway for selective upcycling of PET to arenes - Huiyu Liu; Jun Zhang; Jing Gu; Rui Shan; Haoran Yuan; Yong Chen (Journal of Cleaner Production, 2023)

Rainstorm sediment events in heterogeneous karst small watersheds: Process characteristics, prediction modeling and management enlightenment - Jun Jing; Jiang Yuan; Rui Li; Zaike Gu; Li Qin; Jiayong Gao; Linlv Xiao; Zhenyi Tang; Ling Xiong (Science of The Total Environment, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

A review on the NOx precursors release during biomass pyrolysis - Hongyuan Chen; Rui Shan; Fengxiao Zhao; Jing Gu; Yuyuan Zhang; Haoran Yuan; Yong Chen (Chemical Engineering Journal, 2023)

Knockdown of SOX9 alleviates tracheal fibrosis through the Wnt/β-catenin signaling pathway - Lei Gu; Anmao Li; Jing Lin; Yiling Gan; Chunyan He; Rui Xiao; Jiaxin Liao; Yishi Li; Shuliang Guo (Journal of Molecular Medicine, 2022)

Diversity-oriented synthesis and antifungal activities of novel pimprinine derivative bearing a 1,3,4-oxadiazole-5-thioether moiety - Zi-Long Song; Yun Zhu; Jing-Rui Liu; Shu-Ke Guo; Yu-Cheng Gu; Xinya Han; Hong-Qiang Dong; Qi Sun; Wei-Hua Zhang; Ming-Zhi Zhang (Molecular Diversity, 2021)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Analysis of Mineral Elements, Metabolism, and Inflammation Indexes in the Plasma of Dairy Cows Suffering from Different Degrees of Lameness - Dongbo Sun; Chunqiu Li; Cheng Gu; Jianfei Chen; Yongli Qu; Xinyu Wang; Jing Gao; Shan Wei; Jianfa Wang; Rui Wu; Donghua Guo (Biological Trace Element Research, 2015)

Potential probiotic attributes of a new strain of Bacillus coagulans CGMCC 9951 isolated from healthy piglet feces - Shao-Bin Gu; Li-Na Zhao; Ying Wu; Shi-Chang Li; Jian-Rui Sun; Jing-Fang Huang; Dan-Dan Li (World Journal of Microbiology and Biotechnology, 2015)

Mechanisms underlying low [Ca2+]o-induced increased excitability of hippocampal neurons - Wei-Dong Yue; Yun-Hong Zhang; Feng Gu; Jing Wang; Ji-Ye Zhang; Rui-Min Gu (Neuroscience Bulletin, 2008)

Regulation of skeletal muscle differentiation in fibroblasts by exogenous MyoD gene in vitro and in vivo - Rui-feng Qin; Tian-qiu Mao; Xiao-ming Gu; Kai-jing Hu; Yan-pu Liu; Jin-wu Chen; Xin Nie (Molecular and Cellular Biochemistry, 2007)